The Effect of Total Assets Turnover, Debt to Assets Ratio, Cash Ratio and Current Ratio on Financial Performance of Companies The Hotel, Restaurant and Tourism Subsector in IDX for The Period 2016-2020 - Siti Sarah Chairunisa; Kumba Digdowiseiso; Subur Karyatun (Syntax Corporation Indonesia, 2023)
This study aims to determine and analyze the effect of total assets turnover, debt to assets ratio, cash ratio and current ratio on financial performance of the Hotels, Restaurants and Tourism sub-sector Companies listed on the IDX for the 2016-2020 period. This study uses secondary data by analysing the financial statements of 20 samples of companies, the sampling method using purposive sampling. It show that partially there is a positive and significant effect between total assets turnover and cash ratio on financial performance, while debt to assets ratio has a negative and significant effect on financial performance, and there is no effect between current ratio on financial performance. And research found that there were significant effect between total assets turnover, debt to assets ratio, cash ratio and current ratio on financial performance of the Hotels, Restaurants and Tourism sub-sector Companies listed on the IDX for the 2016-2020 period.